Thermal-repair and high-thermal-conductivity super-hydrophobic coating as well as preparation method and application thereof

By using thermal repair and high thermal conductivity superhydrophobic coatings, the existing coatings have been solved, and a coating with both high thermal conductivity and superhydrophobicity is achieved, which is suitable for heat exchange sites in waste heat recovery processes.

CN119552542APending Publication Date: 2025-03-04HARBIN INST OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411728368.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings have room for optimization in strengthening condensation heat transfer performance, and the thermal conductivity of conventional polymer materials is low, resulting in a decrease in overall thermal conductivity and weakening condensation heat transfer performance.

Method used

The thermally repaired, highly thermally conductive superhydrophobic coating is used, consisting of ethanol solution, dispersant, collagen, polydimethylsiloxane, silica, graphene and polytetrafluoroethylene emulsion. The coating is formed by spraying and staged baking to improve thermal conductivity and superhydrophobicity.

Benefits of technology

It realizes a coating with both high thermal conductivity and superhydrophobicity, improves condensation heat transfer performance, enhances the wear resistance and bonding strength of the coating, and is suitable for heat exchange places in waste heat recovery process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552542A_ABST
    Figure CN119552542A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal repairing and high-thermal-conductivity super-hydrophobic coating and a preparation method and application thereof, and the thermal repairing and high-thermal-conductivity super-hydrophobic coating is formed by thermal repairing and high-thermal-conductivity super-hydrophobic paint. The thermal-repairing and high-thermal-conductivity super-hydrophobic coating is prepared from the following components in parts by mass: 60 to 80 parts of ethanol solution, 1 to 5 parts of dispersing agent, 1 to 5 parts of adherence promoter, 0.3 to 0.5 part of polydimethylsiloxane, 1 to 2 parts of silicon dioxide, 2 to 3 parts of graphene and 15 to 25 parts of polytetrafluoroethylene emulsion. The thermal-repairing and high-thermal-conductivity super-hydrophobic coating disclosed by the invention has a thermal-repairing super-hydrophobic characteristic and excellent thermal conductivity, is suitable for a waste heat recovery process, is used in a place for promoting condensation heat transfer enhancement, and is particularly suitable for heat exchange places such as a vapor-liquid / gas heat exchanger and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating materials, and in particular relates to a thermally repairable, highly thermally conductive super-hydrophobic coating and a preparation method and application thereof. Background Art

[0002] Organic solid waste will produce a lot of waste steam (saturated wet air) during aerobic fermentation. This type of waste heat energy is mostly ignored by people. It has the characteristics of low grade (50-70℃) and long generation cycle. In an environment below 0℃, 60m 3 The heat production rate of the fermentation system can reach 4.7MJ / kg DM, which has great heat recovery potential. At present, using an external heat exchanger to capture fermentation steam is a more efficient waste heat recovery method. The key to improving the heat recovery performance of the system is to strengthen the condensation heat transfer process of the fermentation steam in the heat exchanger.

[0003] For condensation heat transfer inside the heat exchanger, most of the heat and mass transfer is carried out in the form of film condensation. Under the same degree of supercooling, the heat transfer performance during droplet condensation is one order of magnitude higher than that during film condensation. Therefore, promoting the occurrence of droplet condensation can effectively improve the condensation heat transfer performance. By hydrophobic modification of the surface of the heat exchanger plate, film condensation can be converted into droplet condensation. This hydrophobic structure allows the water droplets formed by condensation in the heat exchanger to quickly detach from the heat exchange surface and promote the generation of new water droplets, thereby promoting the process of steam condensation and heat release. In recent years, superhydrophobic coatings have been proven to be very suitable for enhancing condensation heat transfer performance.

[0004] However, there is still a lot of room for optimization and research gaps in super-hydrophobic coatings in terms of enhancing condensation heat transfer. Super-hydrophobic coatings are usually prepared using polymer materials. For example, polytetrafluoroethylene materials, but conventional PTFE coatings have poor adhesion. In addition, the thermal conductivity of such polymer materials is very low (0.1-0.3W / (m·K)), and the thermal conductivity of most metals is 100 times or even 1000 times that of polymers. This results in a significant decrease in the overall thermal conductivity after the coating and the metal heat exchange plate (substrate) are combined, which greatly weakens the condensation heat transfer performance. Although the thermal conductivity of the coating can be effectively improved by doping with some high thermal conductivity fillers, most of these coatings do not have stable super-hydrophobicity, or do not pay attention to its condensation heat transfer performance. At present, there is little research on coatings with both characteristics.

[0005] In addition, in order to promote it in practical applications, it is also necessary to consider the process complexity, coating durability, preparation cost and other issues. Therefore, in order to promote the application of super-hydrophobic coatings in the field of waste heat recovery, it is very necessary to simplify the process to prepare a thermally repairable, highly thermally conductive super-hydrophobic coating. Summary of the invention

[0006] In order to solve one or more technical problems existing in the prior art, the present invention aims to provide a thermally repairable, high thermal conductivity super hydrophobic coating and its preparation method and application. The thermally repairable, high thermal conductivity super hydrophobic coating in the present invention has a thermally repairable super hydrophobic property and excellent thermal conductivity, is suitable for waste heat recovery processes, and is used to promote condensation heat transfer enhancement in places, especially suitable for heat exchange places such as vapor-liquid / gas heat exchangers.

[0007] The present invention provides a thermally repairable, high thermal conductivity super hydrophobic coating in a first aspect, wherein the thermally repairable, high thermal conductivity super hydrophobic coating is formed by a thermally repairable, high thermal conductivity super hydrophobic coating, and the thermally repairable, high thermal conductivity super hydrophobic coating comprises the following components in parts by mass: 60 to 80 parts of ethanol solution, 1 to 5 parts of dispersant, 1 to 5 parts of adhesion agent, 0.3 to 0.5 parts of polydimethylsiloxane, 1 to 2 parts of silicon dioxide, 2 to 3 parts of graphene and 15 to 25 parts of polytetrafluoroethylene emulsion.

[0008] Preferably, the ethanol solution is an ethanol aqueous solution, the volume percentage of ethanol in the ethanol aqueous solution is 80-90%; and / or the solid content of the polytetrafluoroethylene emulsion is 40%-60%.

[0009] Preferably, the dispersant is a sodium polycarboxylate dispersant; the adhesion agent is a modified silane polymer; the silica is silica modified by a silane coupling agent KH-550; and / or the graphene is a few-layer graphene or a single-layer graphene, and preferably, the carbon content in the graphene is not less than 98wt%.

[0010] Preferably, the particle size of the silicon dioxide is not more than 20 nm; and / or the particle size D50 of the graphene is not more than 12 μm.

[0011] In a second aspect, the present invention provides a method for preparing the thermally repairable, highly thermally conductive super-hydrophobic coating according to the first aspect of the present invention, the method comprising the following steps:

[0012] (1) adding a dispersant, an adhesive and polydimethylsiloxane to an ethanol solution and stirring the mixture to obtain a solution A;

[0013] (2) adding silicon dioxide and graphene to solution A and uniformly dispersing them by ultrasonication to obtain solution B;

[0014] (3) adding polytetrafluoroethylene emulsion to solution B and uniformly dispersing by ultrasonication, and then filtering through a sieve with a mesh size of 100 or more to obtain a thermally repairable, highly thermally conductive super-hydrophobic coating;

[0015] (4) The substrate is pretreated, and then the heat-repairable, high-thermal-conductivity super-hydrophobic coating is sprayed on the substrate, and then baked to obtain the heat-repairable, high-thermal-conductivity super-hydrophobic coating on the substrate.

[0016] Preferably, in step (2) and / or step (3), the ultrasonic dispersion time is 10 to 30 minutes.

[0017] Preferably, the spraying is performed under a pressure of 0.2-0.4 MPa, and the distance between the spray gun used during spraying and the substrate is 100-250 mm.

[0018] Preferably, the baking is firstly baking at 250-280° C. for 10-20 min, and then baking at 360-400° C. for 10-30 min; and / or the heating rate to the baking temperature is 5-10° C. / min.

[0019] In a third aspect, the present invention provides a thermally repairable, high thermal conductivity super-hydrophobic coating prepared by the preparation method described in the second aspect of the present invention; preferably, the water contact angle of the thermally repairable, high thermal conductivity super-hydrophobic coating is above 162°, the thermal conductivity is 17.5W / (m·K), the adhesion is level 0 or level 1, and the pencil hardness is above 4H; preferably, the water contact angle of the thermally repairable, high thermal conductivity super-hydrophobic coating after wear and peeling test is above 158.5°, and it still has super-hydrophobicity after 24h of acid-base corrosion test with a pH in the range of 3 to 11; preferably, the thermally repairable, high thermal conductivity super-hydrophobic coating is weakened after liquid erosion, and the super-hydrophobicity is restored after baking at 250°C to 400°C for 5 to 10min.

[0020] In a fourth aspect, the present invention provides an application of the thermally repairable, highly thermally conductive super-hydrophobic coating described in the first aspect of the present invention or the thermally repairable, highly thermally conductive super-hydrophobic coating prepared by the preparation method described in the second aspect of the present invention in the field of waste heat recovery.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] (1) The super hydrophobicity of the heat-repairable and high thermal conductivity super hydrophobic coating in the present invention is mainly provided by silica, graphene, polydimethylsiloxane (PDMS) and polytetrafluoroethylene components, which construct a surface structure with high roughness and low surface energy. The present invention finds that the surface structure with high roughness and low surface energy is also beneficial to improving the super hydrophobic performance of the coating; the high thermal conductivity is mainly provided by graphene and silica components, and two solid fillers of different dimensions are evenly dispersed in the coating to form an interlaced thermal conductive network, which is beneficial to improving the thermal conductivity of the coating; the excellent wear resistance and bonding strength of the heat-repairable and high thermal conductivity super hydrophobic coating in the present invention are mainly enhanced by the adhesive and silica, and the inorganic filler, the metal substrate and the organic resin (polytetrafluoroethylene component) are connected by cross-linking, which effectively improves the adhesion and / or hardness of the coating.

[0023] (2) When preparing the thermal repair and high thermal conductivity super hydrophobic coating of the present invention, the thermal repair and high thermal conductivity super hydrophobic coating can be first obtained by a blending method, and then the thermal repair and high thermal conductivity super hydrophobic coating is formed by a spraying + baking method. The water contact angle of the thermal repair and high thermal conductivity super hydrophobic coating prepared by the present invention can reach 162.7°, and the rolling angle is less than 4°; after coating the coating on a 2.5 mm thick stainless steel plate, the overall thermal conductivity can reach 17.5 W / (m·K), which is higher than that of the stainless steel substrate; it has good adhesion (GB / T9286-1998 standard, grade 0 or 1) and hardness (pencil hardness 4H); after wear and peeling tests, its water contact angle does not change much (158. 5° or above); after a 1-day acid-base corrosion test, it still has super hydrophobicity in the pH range of 3 to 11; in addition, the present invention finds that the silica component in the thermal repair and high thermal conductivity super hydrophobic coating prepared by the present invention has good lipophilicity, has an adsorption effect on the PDMS component, and forms a SiO2@PDMS structure. This SiO2@PDMS structure can give the coating thermal repair performance, which is specifically manifested as follows: after the coating is eroded by liquid (liquid phase erosion) (acid and alkali corrosion, water scouring, etc.), the PDMS component on its surface will be lost, thereby causing its hydrophobicity to weaken, but after a short baking at 250°C to 400°C (5 to 10 minutes), its super hydrophobicity is restored.

[0024] (3) The raw materials used for the thermal repair and high thermal conductivity super hydrophobic coatings of the present invention are low in cost and can be purchased on the market; the preparation process of the thermal repair and high thermal conductivity super hydrophobic coatings of the present invention is simple to operate, and is a simple blending method. The thermal repair and high thermal conductivity super hydrophobic coating can be prepared by a spraying + baking method without the need for specific instruments and equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a wear test result curve of the thermally repairable, high thermal conductivity super-hydrophobic coating obtained in Example 1 of the present invention;

[0026] Figure 2 1 is a peeling test result curve of the thermally repairable, high thermal conductivity super-hydrophobic coating obtained in Example 1 of the present invention;

[0027] Figure 3 is a water impact test result curve of the thermally repaired, highly thermally conductive super-hydrophobic coating obtained in Example 1 of the present invention; Figures 1 to 3 In the figure, the vertical coordinates of the curves on the lower side are all SA; Figures 1 to 3 In the figure, the right ordinate SA is the water sliding angle. Figures 1 to 3 In the figure, the ordinate corresponding to the upper curve is CA (water contact angle), and the ordinate corresponding to the lower curve is SA (water sliding angle);

[0028] Figure 4 This is the result curve of the acid-base corrosion test (chemical stability test) of the thermally repaired, highly thermally conductive super-hydrophobic coating obtained in Example 1 of the present invention;

[0029] Figure 5 1 is a curve of the thermal repair performance test results of the coatings obtained in Example 1 and Example 7 of the present invention; in the figure, the sample without PDMS corresponds to the coating sample obtained in Example 7;

[0030] Figure 6 It is the thermogravimetric curve of the heat-repairable, high thermal conductivity super-hydrophobic coating (PPK-SiO2 / Graphene coating) obtained in Example 1 of the present invention; in the figure, PTFE particles correspond to the results of directly tested polytetrafluoroethylene PTFE particles; PTFE coating corresponds to the results of the coating obtained in the tested comparative example 1; PTFE+15wt%PDMS corresponds to the results of the coating obtained in the tested comparative example 2;

[0031] Figure 7 It is a schematic diagram of the surface structure of the thermally repaired, highly thermally conductive super-hydrophobic coating obtained by the present invention after being damaged;

[0032] Figure 8 It is a diagram of the thermal repair mechanism of the thermally repaired, highly thermally conductive super-hydrophobic coating obtained by the present invention;

[0033] Fig. 9 This is an intuitive thermal conductivity test curve of the thermally repairable, highly thermally conductive super-hydrophobic coating (PPK-SiO2 / Graphene coating) obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In a first aspect, the present invention provides a thermally repairable, high thermal conductivity super hydrophobic coating, wherein the thermally repairable, high thermal conductivity super hydrophobic coating is formed by a thermally repairable, high thermal conductivity super hydrophobic coating, wherein the thermally repairable, high thermal conductivity super hydrophobic coating comprises the following components by mass: 60 to 80 parts (e.g., 60, 65, 70, 75 or 80 parts) of an ethanol solution, 1 to 5 parts (e.g., 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5 parts) of a dispersant, 1 to 5 parts (e.g., 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5 parts) of an adhesive. 5, 3, 3.5, 4, 4.5 or 5 parts), 0.3-0.5 parts (e.g. 0.3, 0.35, 0.4, 0.45 or 0.5 parts) of polydimethylsiloxane (i.e. dimethyl silicone oil), 1-2 parts (e.g. 1, 1.2, 1.5, 1.8 or 2 parts) of silicon dioxide, 2-3 parts (e.g. 2, 2.2, 2.5, 2.8 or 3 parts) of graphene and 15-25 parts (e.g. 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25 parts) of polytetrafluoroethylene emulsion. In the present invention, "parts" refer to "parts by mass". In specific embodiments and comparative examples, the units of parts by mass can be unified as weight units such as "g" or "kg"; in the present invention, for example, a thermally repairable, high thermally conductive super-hydrophobic coating can be prepared by spraying and then baking, and a thermally repairable, high thermally conductive super-hydrophobic coating can be obtained, and a super-hydrophobic coating with high thermal conductivity is quickly constructed; the baking is first baked at 250-280°C (for example, 250°C, 260°C, 270°C or 280°C) for 10-20min (for example, 10, 15 or 20min), and then baked at 360-400°C (for example, 360°C, 370°C, 380°C, 390°C or 400°C) for 10-30min (for example, 10, 15, 20, 25 or 30min); the heating rate to the baking temperature is 5-10°C / min (for example, 5, 6, 7, 8 or 9°C / min).

[0036] The present invention finds that after heat repair and high thermal conductivity super hydrophobic coating are sprayed, the baking method of staged (baking 10-20min+360-400℃ at 250-280℃ for 10-30min) is adopted, the heat repair formed, the performance of high thermal conductivity super hydrophobic coating can be effectively improved, this is because the staged baking used by the present invention helps to gradually remove the solvent and moisture in the coating, reduce the formation of bubbles or pores, the uniform curing of the coating and the discharge of bubbles can be promoted, so as to form a more dense coating structure, it is helpful to improve the super hydrophobic performance and hardness etc. on the surface. In addition, baking at low temperature stage, coating can be better combined with substrate surface, and then baking at high temperature stage for cross-linking or curing, and the adhesion of coating can be enhanced. The super hydrophobicity of the heat-repairable and high thermal conductivity super hydrophobic coating in the present invention is mainly provided by silicon dioxide, graphene, polydimethylsiloxane (PDMS) and polytetrafluoroethylene components, but it is also inseparable from the high roughness and low surface energy surface structure jointly constructed by other components. The present invention finds that the surface structure with high roughness and low surface energy is also beneficial to improving the super hydrophobic performance of the coating; high thermal conductivity is mainly provided by graphene and silicon dioxide components, and two solid fillers of different dimensions are evenly dispersed in the coating to form an interlaced thermal conductive network, which is beneficial to improving the thermal conductivity of the coating, but it is also inseparable from the influence of other components on the formed thermal conductive network structure; the excellent wear resistance and bonding strength of the heat-repairable and high thermal conductivity super hydrophobic coating in the present invention are mainly strengthened by the adhesive and silicon dioxide, and the inorganic filler, the metal substrate and the organic resin (polytetrafluoroethylene component) are connected by cross-linking, which effectively improves the adhesion and / or hardness of the coating, but the other components will also affect the cross-linking. The present invention finds that the content of each component of the thermal repair and high thermal conductivity super-hydrophobic coating needs to be controlled appropriately. If the content of each component is inappropriate, it will have an adverse effect on the super-hydrophobicity, thermal conductivity, wear resistance, mechanical stability and / or adhesion of the coating.

[0037] The thermally repairable, high thermal conductivity super-hydrophobic coating in the present invention has thermally repairable super-hydrophobic properties and excellent thermal conductivity; the present invention is suitable for waste heat recovery processes, and is used in places for promoting condensation heat transfer enhancement, especially for heat exchange places such as vapor-liquid / gas heat exchangers.

[0038] According to some preferred embodiments, the ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 80-90% (for example, 80%, 85% or 90%). In the present invention, the ethanol aqueous solution contains some water, which can hydrolyze the adhesion agent; and / or the solid content of the polytetrafluoroethylene emulsion is 40%-60%. The present invention does not make any specific limitation on the polytetrafluoroethylene emulsion, and commercially available products can be used.

[0039] According to some preferred embodiments, the dispersant is a polycarboxylate sodium salt dispersant; the present invention does not specifically limit the polycarboxylate sodium salt dispersant, for example, a product that can be directly purchased can be used; in some specific embodiments, the polycarboxylate sodium salt dispersant is, for example, a polycarboxylate sodium salt dispersant SN-DISPERSANT 5040; the adhesive is a modified silane polymer; in the present invention, the adhesive is an adhesion promoter, the main component of which is a modified silane polymer, and can also be replaced by a silane coupling agent KH-550; in some specific embodiments, the adhesive can be, for example, an adhesive SRE-6015W, the main component of which is a modified silane polymer; the silica is silica modified by a silane coupling agent KH-550, and the silica modified by a silane coupling agent KH-550 is oleophilic. Hydrophobic silica;The present invention finds that the silica component modified by silane coupling agent KH-550 (3-aminopropyltriethoxysilane) used in the heat repair and high thermal conductivity super hydrophobic coating prepared by the present invention has better lipophilicity and more developed pore structure than unmodified silica, and has suitable adsorption effect on PDMS component to form SiO2@PDMS structure, and this SiO2@PDMS structure can give coating good thermal repair performance;In addition, the type of filler auxiliary agent in the heat repair and high thermal conductivity super hydrophobic coating of the present invention is not to add more the better, the present invention finds that if hardening wear-resistant agent and / or silicon carbide are also mixed in the heat repair and high thermal conductivity super hydrophobic coating, the addition of filling hardening wear-resistant agent and / or silicon carbide will fill a part of the microporous structure, which will affect the diffusion effect of PDMS in the heat repair process, which will affect the heat repairability, but is not conducive to giving the heat-repairable super hydrophobic performance of the coating;The present invention is to silica modified by silane coupling agent KH-550 Without specific limitation, the silica directly purchased or modified by the existing method with silane coupling agent KH-550 can be used; in some specific embodiments, the silica is, for example, silica modified with silane coupling agent KH-550 and having a model number of ZD-SiO2-Z22, which can be purchased from Jinan Zhiding Welding Material Co., Ltd., and has a particle size of preferably 20 nm and a specific surface area of ​​preferably 230 m 2 / g; and / or the graphene is a few-layer graphene or a single-layer graphene, preferably, the graphene is a single-layer graphene, preferably, the carbon content in the graphene is not less than 98wt%.

[0040] According to some preferred embodiments, the silica is silica particles embedded with alumina nanoparticles; the preparation of the silica particles embedded with alumina nanoparticles is as follows: alumina nanoparticles are prepared into an alumina ethanol dispersion with ethanol, wherein the mass fraction of alumina in the alumina ethanol dispersion is 0.1-0.5wt%; silica particles modified with silane coupling agent KH-550 are added to the alumina ethanol dispersion and stirred for 30-60 minutes to ensure that the surface of the silica particles modified with silane coupling agent KH-550 is evenly contacted with alumina nanoparticles to obtain a modified liquid, a solid phase component is separated from the modified liquid, and then the solid phase component is dried at 60-80°C for 1-2 hours, and then sintered at 250-400°C for 1-3 hours to ensure that the alumina nanoparticles are firmly attached to the surface of the silica particles modified with silane coupling agent KH-550, and the silica particles are naturally cooled to room temperature to obtain silica particles embedded with alumina nanoparticles. The present invention finds that it is preferred to introduce the silicon dioxide particles inlaid with the aluminum oxide nanoparticles into the thermal repair, high thermal conductivity super-hydrophobic coating; the present invention finds that although aluminum oxide (Al2O3) nanoparticles are hydrophilic, by introducing them on the surface of the silicon dioxide particles modified by the silane coupling agent KH-550, the surface roughening treatment of the silicon dioxide particles modified by the silane coupling agent KH-550 can be achieved, which is beneficial to the super-hydrophobicity, thermal conductivity, hardness and adhesion of the modified coating; in addition, the present invention finds that the introduction of aluminum oxide nanoparticles significantly increases the specific surface area of ​​the silicon dioxide modified by the silane coupling agent KH-550, while improving the surface roughness, so that it has more adsorption sites and a more developed pore structure, which can provide more physical adsorption sites and better interface bonding for PDMS, which helps to improve its adsorption performance for PDMS and the developed pore structure is also beneficial to the release and decomposition of PDMS to the surface at high temperature, thereby helping to give the coating more excellent thermally repairable super-hydrophobic properties and comprehensive properties.

[0041] According to some preferred embodiments, the particle size of the silicon dioxide is not more than 20 nm; and / or the particle size D50 of the graphene is not more than 12 μm.

[0042] In a second aspect, the present invention provides a method for preparing the thermally repairable, highly thermally conductive super-hydrophobic coating according to the first aspect of the present invention, the method comprising the following steps:

[0043] (1) adding a dispersant, an adhesive and polydimethylsiloxane to an ethanol solution and stirring the mixture to obtain a solution A;

[0044] (2) adding silicon dioxide and graphene to solution A and uniformly dispersing them by ultrasonication to obtain solution B;

[0045] (3) adding polytetrafluoroethylene emulsion to solution B and uniformly dispersing it by ultrasonication, and then filtering it through a sieve with a mesh size of 100 or more to obtain a thermally repairable, highly thermally conductive super-hydrophobic coating; in the present invention, the sieve is, for example, a stainless steel sieve;

[0046] (4) Pre-treating the substrate, spraying the heat-repairable, high thermal conductivity super-hydrophobic coating on the substrate, and then baking to obtain a heat-repairable, high thermal conductivity super-hydrophobic coating on the substrate; in the present invention, the substrate is, for example, a stainless steel and / or copper substrate; the pre-treatment is, for example, cleaning, drying and pre-heating the substrate; in the present invention, the pre-heating is, for example, pre-heating at 80 to 100° C. for 5 to 10 minutes.

[0047] When preparing the thermal repair and high thermal conductivity super-hydrophobic coating, the present invention can first obtain the thermal repair and high thermal conductivity super-hydrophobic coating by a blending method, and then form the thermal repair and high thermal conductivity super-hydrophobic coating by a spraying + baking method. The water contact angle of the thermal repair and high thermal conductivity super-hydrophobic coating prepared by the present invention can reach 162.7°, and the rolling angle is less than 4°; after applying the coating on a 2.5 mm thick stainless steel plate, the overall thermal conductivity can reach 17.5W / (m·K), which is higher than that of the stainless steel substrate; it has good adhesion (GB / T9286-1998 standard, grade 0 or 1) and hardness (pencil hardness 4H); after wear and peeling tests, its water contact angle does not change much (158.5° above); after a one-day acid-base corrosion test, it still has super-hydrophobicity in the pH range of 3 to 11; in addition, the present invention finds that the silica component in the thermal repair and high thermal conductivity super-hydrophobic coating prepared by the present invention has good lipophilicity and a strong adsorption effect on the PDMS component, forming a SiO2@PDMS structure. This SiO2@PDMS structure can give the coating thermal repair performance, which is specifically manifested as follows: after the coating is eroded by liquid (liquid phase erosion) (acid-base corrosion, water scouring, etc.), the PDMS component on its surface will be lost, thereby causing its hydrophobicity to weaken, but after a short baking at 250°C to 400°C (5 to 10 minutes), its super-hydrophobicity is restored. The raw materials used for the thermal repair and high thermal conductivity super hydrophobic coating in the present invention are low in cost and can be purchased on the market; the preparation process of the thermal repair and high thermal conductivity super hydrophobic coating in the present invention is simple to operate, and is a simple blending method. The thermal repair and high thermal conductivity super hydrophobic coating can be prepared by a spraying + baking method without the need for specific instruments and equipment.

[0048] According to some preferred embodiments, in step (2) and / or step (3), the ultrasonic dispersion time is 10 to 30 min (e.g., 10, 15, 20, 25 or 30 min); in the present invention, the ultrasonic dispersion is performed, for example, using an ultrasonic cleaner.

[0049] According to some preferred embodiments, the spraying is carried out under a pressure (air pressure) of 0.2 to 0.4 MPa (for example, 0.2, 0.3 or 0.4 MPa), and the distance between the spray gun used during spraying and the substrate is 100 to 250 mm (for example, 100, 120, 150, 180, 200, 220 or 250 mm); in the present invention, it is preferred to spray at an air pressure of 0.2 to 0.4 MPa, which can ensure that the coating is evenly distributed and effectively covers the surface of the substrate, helping to form a uniform coating and avoid sagging or omissions, and a higher air pressure can better atomize the coating, making the particles smaller, thereby improving the adhesion of the coating, and can improve the spraying efficiency, reduce the waste of coating, and save material costs.

[0050] According to some preferred embodiments, the baking is first baking at 250-280°C (e.g., 250°C, 260°C, 270°C or 280°C) for 10-20 min (e.g., 10, 15 or 20 min), and then baking at 360-400°C (e.g., 360°C, 370°C, 380°C, 390°C or 400°C) for 10-30 min (e.g., 10, 15, 20, 25 or 30 min); and / or the heating rate to the baking temperature is 5-10°C / min (e.g., 5, 6, 7, 8 or 9°C / min). ;The present invention finds that after thermal repair and high thermal conductivity super hydrophobic coating are sprayed, the baking method of staged (baking 10~20min+360~400℃ at 250~280℃ for 10~30min) can be used to effectively improve the performance of the thermal repair and high thermal conductivity super hydrophobic coating formed, because the staged baking used by the present invention helps to gradually remove the solvent and moisture in the coating, reduce the formation of bubbles or pores, and can promote the uniform curing of the coating and the discharge of bubbles, so as to form a more dense coating structure, which helps to improve the super hydrophobic performance and hardness of the surface. In addition, baking at low temperature stage, the coating can be better combined with the substrate surface, and then baking at high temperature stage for cross-linking or curing, and the adhesion of the coating can be enhanced.

[0051] According to some specific embodiments, the preparation of the thermally repairable, highly thermally conductive super-hydrophobic coating is as follows:

[0052] ① In 60 to 80 parts of ethanol aqueous solution with a volume percentage of 80% to 90% ethanol, add 1 to 5 parts of dispersant (polycarboxylic acid sodium salt dispersant SN-DISPERSANT 5040), 1 to 5 parts of adhesive (adhesive SRE-6015W) and 0.3 to 0.5 parts of polydimethylsiloxane (PDMS), stir evenly, and obtain solution A.

[0053] ② In the solution A obtained in step ①, add 1 to 2 parts of silicon dioxide and 2 to 3 parts of graphene fillers, and then disperse them in an ultrasonic cleaner for 10 minutes to obtain solution B; wherein the silicon dioxide is silicon dioxide modified by silane coupling agent KH-550 and has a model of ZD-SiO2-Z22, and the particle size is preferably not more than 20nm; the graphene is a few-layer graphene or a single-layer graphene, preferably a single-layer graphene, the carbon content of the single-layer graphene is not less than 98%, and the particle size D50 is preferably not more than 12μm.

[0054] ③ In the solution B obtained in step ②, 15 to 25 parts of polytetrafluoroethylene emulsion are added while stirring, and then dispersed for 20 minutes through an ultrasonic cleaner, and filtered through a stainless steel mesh of more than 100 meshes to obtain a thermally repairable, high thermal conductivity super-hydrophobic coating; wherein the solid content of the polytetrafluoroethylene emulsion is 40% to 60%.

[0055] ④ After the stainless steel plate and / or copper plate substrate is polished, cleaned, dried and preheated, spray it perpendicular to the plate surface with a spray gun at a distance of 100 to 250 mm from the stainless steel plate and / or copper plate substrate under an air pressure of 0.2 to 0.4 MPa; then bake and shape it in an oven, and set the heating rate to 5 to 10 ° C / min: first increase the temperature to 260 ° C at a heating rate of 5 to 10 ° C / min, and bake it at a constant temperature for 10 to 20 minutes, then increase the temperature to 380 ° C at a heating rate of 5 to 10 ° C / min, bake it at a constant temperature for 10 to 30 minutes, and finally cool it naturally to room temperature, so as to obtain a thermally repaired, high thermal conductivity super hydrophobic coating on the substrate.

[0056] The present invention, in a third aspect, provides a thermally repairable, highly thermally conductive super-hydrophobic coating prepared by the preparation method described in the second aspect of the present invention.

[0057] According to some preferred embodiments, the water contact angle of the thermally repairable, high thermal conductivity super hydrophobic coating is above 162°, the thermal conductivity is 17.5W / (m·K), the adhesion is level 0 or level 1, and the pencil hardness is above 4H; preferably, the water contact angle of the thermally repairable, high thermal conductivity super hydrophobic coating after wear and peeling test is above 158.5°, and it still has super hydrophobicity after 24 hours of acid and alkali corrosion test with a pH range of 3 to 11; preferably, the thermally repairable, high thermal conductivity super hydrophobic coating is weakened after liquid erosion, and the super hydrophobicity is restored after baking at 250°C to 400°C for 5 to 10 minutes.

[0058] In a fourth aspect, the present invention provides an application of the thermally repairable, highly thermally conductive super-hydrophobic coating described in the first aspect of the present invention or the thermally repairable, highly thermally conductive super-hydrophobic coating prepared by the preparation method described in the second aspect of the present invention in the field of waste heat recovery.

[0059] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0060] Example 1

[0061] ① In 70 parts of ethanol aqueous solution with a volume percentage of 85% ethanol, add 3 parts of dispersant (polycarboxylic acid sodium salt dispersant SN-DISPERSANT 5040), 5 parts of adhesive (adhesive SRE-6015W) and 0.5 parts of polydimethylsiloxane (PDMS), stir evenly, and obtain solution A; the polydimethylsiloxane adopts dimethyl silicone oil PMX-200. ② In the solution A obtained in step ①, add 1 part of silicon dioxide and 2 parts of graphene, and then disperse it through an ultrasonic cleaner for 10 minutes to obtain solution B; wherein the silicon dioxide is silicon dioxide modified by silane coupling agent KH-550, model ZD-SiO2-Z22, and particle size is 20nm; the graphene is single-layer graphene, the carbon content of the single-layer graphene is 98wt%, and the particle size D50 is 12μm.

[0062] ③ In the solution B obtained in step ②, 20 parts of polytetrafluoroethylene emulsion were added while stirring, and then dispersed for 20 minutes through an ultrasonic cleaner, and filtered through a 100-mesh stainless steel mesh to obtain a thermally repairable, high thermal conductivity super-hydrophobic coating; wherein the solid content of the polytetrafluoroethylene emulsion was 60%.

[0063] ④ Use a 0.4 mm thick stainless steel plate as a substrate, grind, clean, dry and preheat the stainless steel plate, and then use a spray gun to spray the heat-repaired, high thermal conductivity super hydrophobic coating obtained in step ③ at a distance of 180 mm from the stainless steel plate substrate, perpendicular to the plate surface under an air pressure of 0.3 MPa; then bake and shape in an oven, and the heating rate is set to 5 ° C / min: first, the temperature is increased to 260 ° C at a heating rate of 5 ° C / min, and the temperature is constant temperature baked for 15 minutes, and then the temperature is increased to 380 ° C at a heating rate of 5 ° C / min, and the temperature is constant temperature baked for 25 minutes, and finally naturally cooled to room temperature, that is, a heat-repaired, high thermal conductivity super hydrophobic coating is obtained on the substrate, recorded as PPK-SiO2 / Graphene coating.

[0064] Embodiments 2 to 7

[0065] Examples 2 to 7 are substantially the same as Example 1, except that some components in the adopted formula are different from those in Example 1. The specific differences are shown in Table 1 below.

[0066] Table 1

[0067]

[0068]

[0069] Example 8

[0070] Example 8 is substantially the same as Example 1, except that:

[0071] ② In the solution A obtained in step ①, 1 part of silicon dioxide and 2 parts of graphene are added, and then dispersed in an ultrasonic cleaner for 10 minutes to obtain solution B; wherein the silicon dioxide is silicon dioxide particles embedded with aluminum oxide nanoparticles; the silicon dioxide particles embedded with aluminum oxide nanoparticles are prepared by: preparing aluminum oxide nanoparticles into an aluminum oxide ethanol dispersion liquid with ethanol, wherein the aluminum oxide ethanol dispersion liquid contains 0.3wt% of aluminum oxide by mass; adding silicon dioxide particles modified by silane coupling agent KH-550 to the solution A; The modified solution is obtained by stirring in an alumina ethanol dispersion for 40 minutes, and the solid phase component is separated from the modified solution, and then dried at 70°C for 2 hours, sintered at 300°C for 2 hours, and naturally cooled to room temperature to obtain silica particles embedded with alumina nanoparticles; the silica particles modified by the silane coupling agent KH-550 are silica with a model of ZD-SiO2-Z22 and a particle size of 20nm; the graphene is a single-layer graphene, and the carbon content of the single-layer graphene is 98wt%, and the particle size D50 is 12μm.

[0072] Example 9

[0073] Example 9 is substantially the same as Example 1, except that:

[0074] ② In the solution A obtained in step ①, 1 part of silicon dioxide, 2 parts of graphene and 3 parts of silicon carbide are added, and then dispersed in an ultrasonic cleaner for 10 minutes to obtain solution B; wherein the silicon dioxide is silicon dioxide modified by silane coupling agent KH-550, model ZD-SiO2-Z22, and has a particle size of 20nm; the graphene is a single-layer graphene, the carbon content of the single-layer graphene is 98wt%, and the particle size D50 is 12μm; the particle size of the silicon carbide is 1μm.

[0075] ③ In the solution B obtained in step ②, 1.5 parts of a hardening and wear-resistant agent (hardening and wear-resistant agent SRE-5250, containing 35wt% of SiO2 as an effective ingredient) and 20 parts of a polytetrafluoroethylene emulsion were added while stirring, and then dispersed for 20 minutes using an ultrasonic cleaner, and filtered through a 100-mesh stainless steel mesh to obtain a coating; wherein the solid content of the polytetrafluoroethylene emulsion is 60%; in this embodiment, the coating is used to form a coating in the same manner as step ④ in Example 1.

[0076] Comparative Example 1

[0077] This comparative example provides a commercial polytetrafluoroethylene emulsion as a coating, and adopts the same method as step ④ in Example 1 to form a coating, which is recorded as PTFE coating; wherein the solid content of the polytetrafluoroethylene emulsion is 60%.

[0078] Comparative Example 2

[0079] This comparative example provides a coating, which is obtained by adding polydimethylsiloxane (PDMS) to a polytetrafluoroethylene emulsion, wherein the amount of the polydimethylsiloxane (PDMS) added is 15% of the total mass of the polytetrafluoroethylene emulsion, and the coating is formed into a coating by the same method as step ④ in Example 1, recorded as PTFE+15wt% PDMS coating; wherein the polydimethylsiloxane is dimethyl silicone oil PMX-200, and the solid content of the polytetrafluoroethylene emulsion is 60%.

[0080] Comparative Example 3

[0081] Comparative Example 3 is substantially the same as Example 1, except that:

[0082] ④ A stainless steel plate with a thickness of 0.4 mm is used as a substrate. After the stainless steel plate is polished, cleaned, dried and preheated, the heat-repaired, highly thermally conductive super-hydrophobic coating obtained in step ③ is sprayed perpendicular to the plate surface at a position 180 mm away from the base of the stainless steel plate with a spray gun under an air pressure of 0.3 MPa; then it is baked and formed in an oven, the heating rate is set to 5°C / min, the temperature is increased to 260°C at a heating rate of 5°C / min, and constant temperature baking is performed for 40 minutes, and finally naturally cooled to room temperature to obtain a composite coating on the substrate.

[0083] Comparative Example 4

[0084] Comparative Example 4 is substantially the same as Example 1, except that:

[0085] ④ A stainless steel plate with a thickness of 0.4 mm is used as a substrate. After the stainless steel plate is polished, cleaned, dried and preheated, the heat-repaired, high thermal conductivity super-hydrophobic coating obtained in step ③ is sprayed perpendicular to the plate surface at a position 180 mm away from the base of the stainless steel plate with a spray gun under an air pressure of 0.3 MPa; then it is baked and formed in an oven, the heating rate is set to 5 ° C / min, the temperature is increased to 380 ° C at a heating rate of 5 ° C / min, and the constant temperature baking is performed for 40 minutes, and finally naturally cooled to room temperature to obtain a composite coating on the substrate.

[0086] The present invention performs performance tests on the coatings finally obtained in each embodiment and each ratio, and the test results are shown in Table 2; wherein the water contact angle is the average value of 3 to 5 measurements; the thermal conductivity is the thermal conductivity of the coating formed by spraying the coating in each embodiment or each comparative example on a 2.5 mm thick stainless steel plate using the same method as step ④ in embodiment 1 measured by a laser thermal conductivity meter; the pencil hardness is measured according to GB / T 6739-2022 standard; and the adhesion grade is measured according to GB / T9286-1998 standard.

[0087] Table 2

[0088]

[0089] The present invention conducts mechanical stability and chemical stability tests on the coating (PPK-SiO2 / Graphene coating) obtained in Example 1, and the test method is as follows:

[0090] 1. Wear test: Place the sample face down on 800-grit sandpaper, then place a 150g weight on top of the sample so that the sample test area is in close contact with the sandpaper. Move the sample back and forth 10cm in a specific direction, wear 40cm in each cycle, and record the change in the water contact angle of the sample every 20 cycles. The wear test result curve is as follows: Figure 1 shown.

[0091] 2. Peel test: The coated sample was peeled off with a strong tape (3M 600-1PK model, with an adhesive force of (10±1)N / 25mm), and a weight of 800 grams was placed to ensure complete adhesion of the tape. The change in the water contact angle of the sample was recorded after every 30 peel cycles. The peel test result curve was as follows: Figure 2 shown.

[0092] 3. Water impact test: The coating sample is fixed on a 45° inclined surface, and water drops continuously fall from a height of 50 cm at a speed of 20 mL / min. The wettability (water contact angle) of the sample is recorded once every 30 minutes. The water impact test result curve is as follows: Figure 3 shown.

[0093] 4. Chemical stability test: Use HCl solution / NaOH solution with pH=1-13 to corrode the coating surface for 24 hours, test the water contact angle of the coating after corrosion, and measure the acid-base corrosion test (chemical stability test) result curve as shown below: Figure 4 As shown, the result corresponding to pH=7 is the result obtained by corroding the coating surface with a 3.5wt% NaCl aqueous solution for 24 hours.

[0094] Depend on Figures 1 to 4The results show that after the chemical stability test, the contact angle of the PPK-SiO2 / Graphene coating can be maintained above 145.3°. Among them, its mechanical stability is even better; the water impact resistance of the coating is relatively poor, but the super-hydrophobic structure can still be maintained during the test; in the alkali corrosion test, the surface hydrophobic structure will be destroyed after a long period of strong alkali corrosion (pH not less than 13, corrosion time greater than 24h), and the super-hydrophobic structure can be maintained in the pH range of 3 to 11. Obviously, after liquid phase erosion, the hydrophobicity of the coating is weakened. The reason is the loss of PDMS components on the coating surface. Mechanical damage has little effect on the hydrophobicity of the coating. The reason is that after the surface structure of the coating is peeled off, the PDMS component is exposed along with the new surface, showing a stable super-hydrophobicity.

[0095] The present invention conducted a thermal repair test on the coating. The test method is: the coatings in Example 1 and Example 7 after water washing (water washing for 300 minutes) and acid-base corrosion (acid pH = 1 corrosion for 24 hours and alkaline pH = 13 corrosion for 24 hours) were baked at a certain temperature (at 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C) for 10 minutes, and the change in water contact angle before and after baking was tested. The results are as follows: Figure 5 As shown; Figure 5 The results show that Example 1 exhibits thermal repairability at 250°C to 400°C, and can be restored to a superhydrophobic state after baking at above 300°C, with a contact angle of more than 151.9°. However, Example 7 does not exhibit thermal repairability. Obviously, the thermal repairability of the coating is related to the PDMS component. The present invention shows through thermogravimetric analysis (the results are shown in Figure 6 As shown in the figure, the PTFE particles and PTFE coatings used only began to lose weight significantly at 450-500°C, and the baking at 200-400°C had little effect on the PTFE component. The PTFE+15wt% PDMS coating and the PPK-SiO2 / Graphene coating lost weight slightly at 300-400°C, in which PDMS was one of the main weight-losing components. At the same time, compared with the PTFE+15wt% PDMS coating, the weight-losing temperature of the PPK-SiO2 / Graphene coating was higher, which was presumably caused by the doping of silicon dioxide and graphene. The silicon dioxide used in Example 1 of the present invention has strong lipophilicity and a developed pore structure, which enables silicon dioxide to adsorb PDMS. The present invention combines the results of thermogravimetric analysis and thermal repair experimental tests to analyze the thermal repair mechanism of the coating in the present invention as follows: PDMS is partially adsorbed in the pores of silica. During the heating process, PDMS is first released from the pores and then decomposed into oligomers with hydrophobic groups and diffused to the damaged surface. The schematic diagram of the surface structure of the thermally repairable, highly thermally conductive super-hydrophobic coating obtained by the present invention after damage is shown in FIG. Figure 7 As shown in FIG. 1 , the thermal repair mechanism diagram of the thermally-repaired, highly thermally-conductive super-hydrophobic coating obtained by the present invention is as follows: Figure 8 shown.

[0096] The present invention uses the same method as above to carry out thermal repair experimental tests on the coatings obtained in Examples 8 to 9. It is found that after water scouring (water scouring for 300 minutes) and acid-base corrosion (acid pH=1 corrosion for 24 hours and alkaline pH=13 corrosion for 24 hours), the coating in Example 8 exhibits thermal repair properties like Example 1, and can be restored to the super-hydrophobic state before being corroded by the liquid phase after baking at above 300°C for 10 minutes, with a contact angle of more than 160°. However, the coating in Example 9 does not exhibit thermal repair properties like Example 7.

[0097] The present invention also conducted an intuitive thermal conductivity test on the coating. The test method is: the coating and the stainless steel substrate (0.4mm thick) in the comparative example 1 and the embodiment 1 are placed on a 100°C heating table, and an open water bottle containing 20mL of water is placed on the sample. The water temperature change is recorded at regular intervals, and the results are as follows: Fig. 9 shown. Fig. 9 The results show that the water heating effect is in the order of Example 1 > stainless steel > comparative example 1, which indirectly reflects that the coating in Example 1 (PPK-SiO2 / Graphene coating) has excellent thermal conductivity, that is, the thermal conductivity of the stainless steel substrate can be significantly improved by coating the PPK-SiO2 / Graphene coating.

[0098] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A thermally repairable, highly thermally conductive super-hydrophobic coating, characterized in that: The thermally repairable, high thermal conductivity super-hydrophobic coating is formed by a thermally repairable, high thermal conductivity super-hydrophobic coating, and the thermally repairable, high thermal conductivity super-hydrophobic coating comprises the following components in parts by mass: 60-80 parts of ethanol solution, 1-5 parts of dispersant, 1-5 parts of adhesion agent, 0.3-0.5 parts of polydimethylsiloxane, 1-2 parts of silicon dioxide, 2-3 parts of graphene and 15-25 parts of polytetrafluoroethylene emulsion.

2. The thermally repairable, highly thermally conductive super-hydrophobic coating according to claim 1, characterized in that: The ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 80-90%; and / or The solid content of the polytetrafluoroethylene emulsion is 40% to 60%.

3. The thermally repairable, highly thermally conductive super-hydrophobic coating according to claim 1, characterized in that: The dispersant is a polycarboxylate sodium salt dispersant; The adhesive is a modified silane polymer; The silicon dioxide is silicon dioxide modified by silane coupling agent KH-550; and / or The graphene is a few-layer graphene or a single-layer graphene. Preferably, the carbon content in the graphene is not less than 98 wt %.

4. The thermally repairable, highly thermally conductive super-hydrophobic coating according to claim 1, characterized in that: The particle size of the silicon dioxide does not exceed 20 nm; and / or The particle size D50 of the graphene is no more than 12 μm.

5. The method for preparing a heat-repairable, highly thermally conductive super-hydrophobic coating according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) adding a dispersant, an adhesive and polydimethylsiloxane to an ethanol solution and stirring the mixture to obtain a solution A; (2) adding silicon dioxide and graphene to solution A and uniformly dispersing them by ultrasonication to obtain solution B; (3) adding polytetrafluoroethylene emulsion to solution B and uniformly dispersing by ultrasonication, and then filtering through a sieve with a mesh size of 100 or more to obtain a thermally repairable, highly thermally conductive super-hydrophobic coating; (4) The substrate is pretreated, and then the heat-repairable, high-thermal-conductivity super-hydrophobic coating is sprayed on the substrate, and then baked to obtain the heat-repairable, high-thermal-conductivity super-hydrophobic coating on the substrate.

6. The preparation method according to claim 5, characterized in that: In step (2) and / or step (3), the ultrasonic dispersion time is 10 to 30 minutes.

7. The preparation method according to claim 5, characterized in that: The spraying is carried out under the condition of a pressure of 0.2-0.4 MPa, and the distance between the spray gun used during the spraying and the substrate is 100-250 mm.

8. The preparation method according to claim 5, characterized in that: The baking is firstly baking at 250-280°C for 10-20min, and then baking at 360-400°C for 10-30min; and / or The heating rate to the baking temperature is 5 to 10°C / min.

9. A thermally repairable, highly thermally conductive super hydrophobic coating prepared by the preparation method according to any one of claims 5 to 8; Preferably, the water contact angle of the thermally repairable, highly thermally conductive super-hydrophobic coating is above 162°, the thermal conductivity is 17.5W / (m·K), the adhesion is level 0 or 1, and the pencil hardness is above 4H; Preferably, the thermally repairable, highly thermally conductive super-hydrophobic coating has a water contact angle of more than 158.5° after abrasion and peeling tests, and still has super-hydrophobicity after a 24-hour acid-base corrosion test at a pH range of 3 to 11; Preferably, the thermally repairable, high thermal conductivity super-hydrophobic coating has its hydrophobicity weakened after being eroded by liquid, and its super-hydrophobicity is restored after being baked at 250° C. to 400° C. for 5 to 10 minutes.

10. Application of the thermally repairable, highly thermally conductive super-hydrophobic coating according to any one of claims 1 to 4 or the thermally repairable, highly thermally conductive super-hydrophobic coating prepared by the preparation method according to any one of claims 5 to 8 in the field of waste heat recovery.

Citation Information

Patent Citations

  • Superhydrophobic composite coating with self-repair function and preparation method thereof

    CN105038439A

  • Anti-frosting super-hydrophobic coating for evaporator and preparation method of anti-frosting super-hydrophobic coating

    CN116239919A

  • Super-hydrophobic cotton fabric with self-healing function and preparation method thereof

    CN118498074A